Mitral valve repair for post-myocardial infarction papillary muscle rupture - Bouma, Wobbe (Oxford University Press, 2013)
OBJECTIVES: Papillary muscle rupture (PMR) is a rare, but serious mechanical complication of myocardial infarction (MI). Although mitral valve replacement is usually the preferred treatment for this condition, mitral valve repair may offer an improved outcome. In this study, we sought to determine the outcome of mitral valve repair for post-MI PMR and to provide a systematic review of the literature on this topic. METHODS: Between January 1990 and December 2010, 9 consecutive patients (mean age 63.5 ± 14.2 years) underwent mitral valve repair for partial post-MI PMR. Clinical data, echocardiographic data, catheterization data and surgical reports were reviewed. Follow-up was obtained in December of 2012 and it was complete; the mean follow-up was 8.7 ± 6.1 (range 0.2–18.8 years). RESULTS: Intraoperative and in-hospital mortality were 0%. Intraoperative repair failure rate was 11.1% (n = 1). Freedom from Grade 3+ or 4+ mitral regurgitation and from reoperation at 1, 5, 10 and 15 years was 87.5 ± 11.7%. Estimated 1-, 5-, 10- and 15-year survival rates were 100, 83.3 ± 15.2, 66.7 ± 19.2 and 44.4 ± 22.2%, respectively. There were 3 late deaths, and 2 were cardiac-related. All late survivors were in New York Heart Association Class I or II. No predictors of long-term survival could be identified. CONCLUSIONS: Mitral valve repair for partial or incomplete post-MI PMR is reliable and provides good short- and long-term results, provided established repair techniques are used and adjacent tissue is not friable. PMR type and adjacent tissue quality ultimately determine the feasibility and durability of repair.